2017
DOI: 10.1039/c6ra28599f
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient one-pot three-component Betti reaction in water using reverse zinc oxide micelles as a recoverable and reusable catalyst

Abstract: An efficient synthesis of Betti basesviaa one-pot three-component reaction of 2-naphthol, substituted aldehydes and anilines in aqueous media is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Pei et al 100 reported a highly efficient one-pot threecomponent Betti reaction using reverse ZnO micelles as a recoverable and reusable catalyst. Reactions were conducted with 2-naphthol, aromatic aldehydes, amines and reverse ZnO nanomicelles (10 mol%) in water at room temperature within 4-60 min, affording Betti base derivatives 134 in 29-96% yields (Scheme 91).…”
Section: Synthesis and Synthetic Applications Of Betti Base Derivativesmentioning
confidence: 99%
“…Pei et al 100 reported a highly efficient one-pot threecomponent Betti reaction using reverse ZnO micelles as a recoverable and reusable catalyst. Reactions were conducted with 2-naphthol, aromatic aldehydes, amines and reverse ZnO nanomicelles (10 mol%) in water at room temperature within 4-60 min, affording Betti base derivatives 134 in 29-96% yields (Scheme 91).…”
Section: Synthesis and Synthetic Applications Of Betti Base Derivativesmentioning
confidence: 99%
“…ZnO NPs were synthesized using the modified reversed-phase microemulsion method which utilized zinc acetate as precursor (Mou et al., 2017). Briefly, hexadecyl trimethyl ammonium bromide (CTAB, 0.3644 g, 1 mmol) was dissolved in cyclohexane (10 mL).…”
Section: Methodsmentioning
confidence: 99%
“…The reverse zinc oxide nanomicelles was synthesized following the reported procedure (Mou et al, 2017) (Scheme 2). Reverse micelles were formed by the self-assembly of the surfactant in cyclohexane.…”
Section: Preparation and Characterization Of Catalystmentioning
confidence: 99%
“…Our previous studies have shown that the Betti reaction could be promoted by reverse zinc oxide micelles in aqueous efficiently and selectively (Mou et al, 2017). As interest continues in the potential use of such a catalyst, we report herein a simple, one-pot synthesis of 2-substituted 2,3-dihydroquinazolin-4(1H)-one from substituted aldehydes and anthranilamide in the presence of reverse zinc oxide micelles as a catalytic system (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%